2015
DOI: 10.1002/tox.22188
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and endocytosis are involved in upregulation of interleukin-8 expression in airway cells exposed to PM2.5

Abstract: Inhaled PM2.5 (particulate matter with an aerodynamic diameter of 2.5 μm or less) can induce lung inflammation through released inflammatory mediators from airway cells, such as interleukin-8 (IL-8) and tumor necrosis factor alpha (TNF-α). However, the mechanisms underlying PM2.5-induced IL-8 gene expression have not been fully characterized. BEAS-2B cells (a human bronchial epithelial cell line) and THP-1 cells (a human macrophage-like cell line) were used as the in vitro models to investigate the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…Endocytotic uptake mechanisms or activation of PPR, for instance, are required for the induction of airway epithelial cytokine release upon PM exposure. Addition of CytoD, an inhibitor of actin‐dependent uptake mechanisms, resulted in a significant reduction in PM‐induced IL‐8 and GM‐CSF levels, whereas a blocking antibody to TLR2 inhibited the PM‐induced IL‐8 expression . Moreover, DEPs‐induced IL‐8 and GM‐CSF release were blocked by neutralizing antibodies towards EGFR or autocrine ligands of the EGFR, indicating that activation of the EGFR is an important pathway in DEPs‐induced cytokine release .…”
Section: How Does Particulate Matter Influence Epithelial Cytokine Exmentioning
confidence: 99%
See 2 more Smart Citations
“…Endocytotic uptake mechanisms or activation of PPR, for instance, are required for the induction of airway epithelial cytokine release upon PM exposure. Addition of CytoD, an inhibitor of actin‐dependent uptake mechanisms, resulted in a significant reduction in PM‐induced IL‐8 and GM‐CSF levels, whereas a blocking antibody to TLR2 inhibited the PM‐induced IL‐8 expression . Moreover, DEPs‐induced IL‐8 and GM‐CSF release were blocked by neutralizing antibodies towards EGFR or autocrine ligands of the EGFR, indicating that activation of the EGFR is an important pathway in DEPs‐induced cytokine release .…”
Section: How Does Particulate Matter Influence Epithelial Cytokine Exmentioning
confidence: 99%
“…Importantly, after internalization or PRR activation, exposure to ambient PM/DEPs will activate oxidative stress responses in the airway epithelial cells. When lung epithelial cells are exposed to ambient PM/DEPs higher levels of intracellular ROS formation, activation of oxidative stress‐responsive genes, such as HMOX1, and oxidative damage has been demonstrated . Ambient PM/DEPs exposure was further associated with the overexpression of several genes and increased phosphorylated proteins related to the MAPK or PI3K/AKT pathway .…”
Section: Air Pollution and The Airway Epitheliummentioning
confidence: 99%
See 1 more Smart Citation
“…Following the discovery of the potential importance of isoprene SOA in generating ROS, Lin et al (2016) showed that isoprene SOA formed from the reactive uptake of epoxides alters levels of oxidative stress-associated genes, including COX-2 in human lung cells. Oxidative stress caused by ROS plays a major role in lung inflammation and the induction of oxidative stress can lead to IL-8 expression (Tao et al, 2003;Yan et al, 2015). Specifically, oxidants can activate the transcription factor NF-κB, which regulates a wide range of inflammatory genes including IL-8 and COX-2 (Barnes and Adcock, 1997; Schreck et al, 1992).…”
Section: Biological Implicationsmentioning
confidence: 99%
“…The oxidative stress induced by excessive levels of ROS could cause further induction of inflammatory mediators, DNA damage and apoptosis. These effects may cause downstream molecular events that trigger vasculature permeabilization and, eventually, cardiovascular disorders (Yan et al, 2015;Tseng et al, 2016). There are some fragmentary studies that have also indicated that the association between PMassociated metals and biological processes is related to oxidative stress and other biological processes.…”
Section: Effects Of Heavy Metal-containing Pm 25 On H9c2 Cell Apoptosismentioning
confidence: 97%